Repair and Maintenance of Ceramic Mould Pressing Machine: Perbaikan dan Perawatan Mesin Pressing Cetak Keramik - Putra, Bagas; Mulyadi, Mulyadi (Procedia of Engineering and Life Science, 2024)
This study delves into the critical maintenance and repair procedures for ceramic pressing machines, integral to ceramic tile production. Through a comprehensive review of techniques and best practices, the research aims to optimize machine efficiency and quality output. Employing a methodical approach involving regular cleaning, component inspection, and timely part replacement, the study underscores the significance of skilled technicians proficient in diagnosing and rectifying issues before they escalate. Furthermore, emphasis is placed on the necessity of rigorous training for maintenance personnel and machine operators to ensure seamless operations and minimal production disruptions. The implications of these findings extend to the broader manufacturing sector, offering insights into enhancing machinery longevity and productivity. highlight : Proper maintenance ensures smooth operation and prevents unexpected breakdowns. Trained technicians are essential for effective repair and troubleshooting. Rigorous training for maintenance staff and operators optimizes machine performance and minimizes production downtime. Keywords: Ceramic pressing machines, Maintenance, Repair, Efficiency, Training